(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: Chronic lymphocytic leukemia (CLL) is a hematological malignancy characterized by the accumulation of immunologically mature cluster of differentiation (CD) 5+ B-lymphocytes in the blood, bone marrow and lymphatic tissues. Hyperthyroidism can occasionally be caused by non-thyroid cancers infiltrating the thyroid and cause hyperthyroidism. Objective: To assess the thyroid function of patients with CLL. Methods: Patients and participant controls are subjected to prevalence tests of thyroid function as thyroid stimulating hormone (TSH), thyroxine (T4) and triiodothyronine (T3). Serum samples were analyzed by specialized kits of immunodiagnostic mini VIDAS Industry system (BioMérieux, France). Results: Out of 37 males and 17 females CLL patients and 60 volunteer controls (36 males and 24 females), only two male patients at their sixth decade were diagnosed with hyperthyroidism, these patients were classified as Stage (A) to the Binet staging system. The test results were showed as follow: TSH;